T lymphocytes migrate upstream after completing the leukocyte adhesion cascade. Issue 1 (1st January 2019) - Anderson, Nicholas R.; Buffone, Alexander; Hammer, Daniel A.
ABSTRACT: The leukocyte adhesion cascade is of critical importance for both the maintenance of immune homeostasis and the ability of immune cells to perform effector functions. Here, we present data showing CD4 + T cells migrate upstream (against the direction of flow) after completing the leukocyte adhesion cascade on surfaces displaying either ICAM-1 or ICAM-1 and VCAM-1, but migrate downstream on surfaces displaying only VCAM-1. Cells completing the cascade on HUVECs initially migrate upstream before reverting to more random migration, partly caused by transmigration of cells migrating against the flow. Furthermore, cells migrating upstream transmigrate faster than cells migrating downstream. On HUVECs, blocking interactions between LFA-1 and ICAM-1 resulted in downstream migration and slower transmigration. These results further suggest a possible physiological role for upstream migration in vivo .